Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would you prove the following? $$\lim_{n \rightarrow \infty} (1+c/n^2 - 2/n)^n = e^{-2}$$

where $c\geq 1$ is a constant.

I can find proofs online of $\lim_{n \rightarrow \infty} (1-2/n)^n = e^{-2}$ but how do you make the above rigorous?

share|cite|improve this question
Hint: $(1 + \frac{1}{n^2} - \frac{2}{n}) = (1-\frac{1}{n})^2$. – froggie Dec 13 '12 at 14:31
Edited question slightly (but thanks). – Sprong Dec 13 '12 at 14:35
up vote 4 down vote accepted

Note that

$$\frac 1 {n^2}-\frac 2 n +1=\left(\frac 1 n -1\right)^2$$


Let $$x_n= \left(1- \frac 2 n+\frac c {n^2}\right)^n $$

so that $$y_n=\log x_n=n \log \left(1- \frac 2 n+\frac c {n^2}\right)$$


$$n{\log \left(1- \frac 2 n+\frac c {n^2}\right)}=$$

$$n\left(\frac c {n^2}- \frac 2 n\right)\frac{\log \left(1+\left(\frac c {n^2}- \frac 2 n\right)\right)}{\left(\frac c {n^2}- \frac 2 n\right)}=$$

$$\left(\frac c {n}- 2\right)\frac{\log \left(1+a_n\right)}{a_n}=$$

Now $a_n\to 0$; so that

$$\left(\frac c {n}- 2\right)\frac{\log \left(1+a_n\right)}{a_n}\to (0-2)\cdot 1 =-2$$

This means $x_n\to e^{-2}$

share|cite|improve this answer
Edited question to make it clearer that I am interested in not just $c=1$. – Sprong Dec 13 '12 at 14:33
@Sprong Thanks. You need to use that $\log(1+x)/x$ tends to $1$ which also needs a proof I suppose. – Sprong Dec 13 '12 at 15:09
I am using that. You can find various proofs of that, or give one yourself. – Pedro Tamaroff Dec 13 '12 at 15:18

$$\lim _{n\to\infty} \left(\left(1+\frac{c-2n}{n^2}\right)^{\frac{n^2}{c-2n}}\right)^{\frac{c-2n}{n}}$$

$$= \left(\lim _{n\to\infty}\left(1+\frac{c-2n}{n^2}\right)^{\frac{n^2}{c-2n}}\right)^{\lim _{n\to\infty}\left(\frac{c-2n}n\right)}$$

$$= \left(\lim _{m\to\infty}\left(1+\frac1m\right)^m\right)^{\lim _{n\to\infty}\left(\frac{c-2n}n\right)}$$ where $m=\frac{n^2}{c-2n},n\to \infty\implies m\to\infty$

$$=e^{-2}$$ for any finite value of $c$

share|cite|improve this answer
Can you explain this a little more please? – Sprong Dec 13 '12 at 14:40
@Sprong, please find the edited answer. – lab bhattacharjee Dec 13 '12 at 14:44
I am a little worried about the part where you put a limit also in the exponent. How do we know that is valid? – Sprong Dec 13 '12 at 14:45
@Sprong, please use logarithm if you are not comfortable with exponent. – lab bhattacharjee Dec 13 '12 at 14:46

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.